Revisiting Methaqualone: Changes Made and Future Lessons Ignored - Griffin, O. Hayden (American journal of criminal justice, 2022)
Methaqualone, a sedative-hypnotic drug, was legally available in the United States for less than twenty years. During that time, millions of doses were prescribed to patients and an untold number of pills were taken by recreational users. In what has become a common theme among many pharmaceutical products, methaqualone sales and use were heavily influenced by a widespread and misleading marketing campaign. After methaqualone was placed into Schedule I of the Controlled Substances Act, in 1984, use of the drug diminished until methaqualone became essentially nonexistent in the United States. While some have concluded that the disappearance of methaqualone was a regulatory success, we argue that drug regulators myopically focused on methaqualone itself and did not give enough consideration to how other drugs could produce equal or greater levels of harm and no actions were taken to disincentivize and/or prevent the pharmaceutical industry from engaging in similar behaviors.